Investigation of environment waste resultant from incorrect excretion of stock car rubbers and determination quantity, a current situation and fate of them (a case study: Ahvaz, Iran) - Eslami, Mohsen; Raof, Farzaneh Fakeri; Zadeh, Mohammad Jorjor (Ciência e Natura, 2015)
A healthy environment is an absolute necessity for the well-being of all governments' policy. The population on the earth is expanding rapidly which goes hand in hand in the degradation of the environment at large measures. The human’s appetites for needs are disarranging the environments natural equilibrium. Growth of automobile industry in the world due to dignity to the parallel with increasing the production of rubber in the world. So increasing the disposal of worn tires is one of the world's great challenges. Annually, large amount of rubbers in the world is prepared. The rubber used in normal conditions can't be easily decomposed and make environmental pollution. This study was performed in Ahvaz metropolitan. The information in this study was achieved by questionnaire were asked of 40 shops, who was activated in the tire field. After this research revealed turned out about 300 shops were activated in the field of tires at the time of this study(2014), Also revealed 2700 tire rings out of cycle per day in Ahvaz .in this study (68%) questionnaire, believed that the tires after release from the workshop are collected by badger. (22%) believed that collected by municipal. Also (7%) of questionnaire believed that they didn't have any information about the release tires. At least only (3%) believed that himself collect damaged tires in their workshops. The application of the tire after collection in the idea of responded following: 15 person of questionnaire believe the tires sold after release from the workshop. 9 person said tires left in the wild. 8 persons believed that tires buried in a special place, Also 6 persons of questionnaire believed that tires are getting burned. At the end 2 persons of questionnaire believed that they don't know the fate of tires. At least some of the environmental hazards caused by incorrect tire were buried as were recommendation to improve.